Exploring Preterm Birth as a Polymicrobial Disease: An Overview of the Uterine Microbiome - Payne, Matthew S.; Bayatibojakhi, Sara (Frontiers in Immunology, 2014)
Infection is the leading cause of preterm birth. A focus of many studies over the past decade has been to characterise microorganisms present in the uterine cavity and document any association with negative pregnancy outcome. A range of techniques have been used to achieve this, including microbiological culture and targeted polymerase chain reaction assays, and more recently, microbiome-level analyses involving either conserved, phylogenetically informative genes such as the bacterial 16S rRNA gene or whole shotgun metagenomic sequencing. These studies have contributed vast amounts of data towards characterisation of the uterine microbiome, specifically that present in the amniotic fluid, fetal membranes and placenta. However, an overwhelming emphasis has been placed on the bacterial microbiome, with far less data produced on the viral and fungal/yeast microbiomes. With numerous studies now referring to preterm birth as a polymicrobial condition, there is the need to investigate the role of viruses and fungi in more detail and in particular, look for associations between colonisation with these microorganisms and bacteria in the same samples. Although the major pathway by which microorganisms are believed to colonise the uterine cavity is vertical ascension from the vagina, numerous studies are now emerging suggesting haematogenous transfer of oral microbiota to the uterine cavity. Evidence of this has been produced in mouse models and although DNA-based evidence in humans appears convincing in some aspects, use of methodologies that only detect viable cells as opposed to lysed cells and extracellular DNA are needed to clarify this. Such techniques as RNA analyses and viability PCR are likely to play key roles in the clinical translation of future microbiome-based data, particularly in confined environments such as the uterus, as detection of viable cells plays a key role in diagnosis and treatment of infection.